EMPHYSEMATOUS PYELONEPHRITIS; REPORT OF A CASE CONSENT - Muaz; Hassan Ali Choudry; Asadullah Lughari (Journal of University Medical & Dental College, 2015)
ABSTRACT: Emphysematous pyelonephritis is rare life threatening condition produced in diabetics [1] after a few years of uncontrolled glycosuria resulting in the action of gas producing bacteria forming air cavities (hence the name) in the kidney. The generally sought treatment for EPN is nephrectomy. We present a case of a female patient presented with complaints of Fever and severe left flank pain for many days treated conservatively and was cured after 23 days. We aspire to enlighten other urologists of the case and is conservative treatment.